Home-Based Phototherapy Versus Hospital-Based Phototherapy for Treatment of Neonatal Hyperbilirubinemia: A Systematic Review and Meta-Analysis. (June 2020) - Chu, Liangliang; Qiao, Jianhong; Xu, Cuiping
Objective. Phototherapy devices have been found to be an effective method for treating neonatal hyperbilirubinemia. We reviewed the current literature to determine whether home-based phototherapy is more effective than hospital-based phototherapy for the treatment of neonatal hyperbilirubinemia. Method. PubMed, Scopus, Embase, Cochrane library, CBM, CNKI, and Wanfang Data were searched to collect the comparative study of home-based phototherapy versus hospital-based phototherapy for the treatment of neonatal hyperbilirubinemia. All studies were found to be of low risk based on Cochrane Collaborative Risk of Bias Tool. Data were statistically extracted and evaluated by RevMan 5.3 software. Result. A total of 259 neonates were included in the meta-analysis. Compared with hospital-based phototherapy, home-based phototherapy appeared more effective for the treatment of neonatal hyperbilirubinemia in reducing the rate of total serum bilirubin (standard mean difference = 0.32, 95% confidence interval = −0.22 to 0.86, P = .04); however, there was no signiﬁcant difference in duration of phototherapy (standard mean difference = 0.59, 95% confidence interval = 0.28 to 0.90, P = .06) in the 2 groups. Conclusion. Home-based phototherapy was more effective than hospital-based phototherapy in treatment for neonatal hyperbilirubinemia; home-based phototherapy is an effective, feasible, safe, and alternative to hospital-based phototherapy for neonatal hyperbilirubinemia.